Capital accumulation and unemployment: New insights in the Nordic experience - Marika Karanassou; Hector Sala; Pablo F. Salvador (Queen Mary University of London, Department of Economics, 2007)
This paper takes a fresh look at the analysis of labour market dynamics and argues that capital accumulation plays a fundamental role in shaping unemployment movements. This role has generally been examined by considering indirect transmission channels of the capital stock effects, i.e. using variables like interest rates or investment ratios in the estimation of single-equation unemployment rate models. Here we advocate a different approach. We directly estimate the effects of capital stock in the labour market by applying the chain reaction theory of unemployment, and we find that capital stock is a major determinant of unemployment in the Nordic countries. In particular, the different unemployment experiences of these economies derive from the temporary (albeit prolonged) negative shocks to capital stock growth in Denmark and Sweden, and the permanent downturn of capital stock growth in Finland. We are thus able to explain why the crisis of the early 1990s had a more accute impact in Finland than in its twin economy, Sweden.
Keywords: E22; E24; J21; 330; Unemployment dynamics; Chain reaction theory; Capital accumulation; Nordic countries; Gesamtwirtschaftliches Anlageverm\~AƒÂgen; Investition; Arbeitslosigkeit; D\~AƒÂnemark; Finnland; Schweden